Key Technologies for 5G/6G Mobile Fronthaul Network - ZHU Yiming; LIN Xianhao; CHI Nan; SHI Jianyang (Guangtongxin yanjiu)
As the 5th Generation Network (5G) technology evolves towards the 6th Generation Network (6G), Mobile Fronthaul (MFH) networks are encountering new demands for increased speed and capacity. Currently, there exist several methods for constructing these networks, including wired Common Public Radio Interface (CPRI), enhanced Common Public Radio Interface (eCPRI), Radio over Fiber (RoF) communication, wireless Free Space Optical (FSO) communication, as well as full-band access and Artificial Intelligence (AI) technology for 6G. This article focuses on the foundational architecture of MFH networks, exploring various construction technologies, analyzing their strengths, weaknesses, and proposed solutions. By doing so, we provide valuable insights for future research on high-speed and high-capacity MFH networks.